THE ROLE OF THE CD8+:CD3+ RATIO OF CELL DIFFERENTIATION MARKERS IN LYMPHOCYTIC INFILTRATES OF THE SKIN WITH MYCOSIS FUNGOIDES - Hamade Luay Mustafa (Bogomolets National Medical University, 2016)
Histological diagnosis of mycosis fungoides is complicated, particularly during the early clinical manifestations of skin disease where changes can be interpreted as a banal inflammation. Histopathology of mycosis fungoides is characterized by the formation in the upper dermal of lymphocytic infiltrates as a result of clonal proliferation of tumor epidermotropic CD4+ lymphocytes with a small percentage of CD8 + cells. The vast predominance of CD4+ lymphocytes in skin infiltrate and an increase the ratio of CD4+:CD8+ is the main criterion of mycosis fungoides diagnosis. However, histiocytes, involved in the formation of inflammatory infiltrate, also have CD4 positivity the same as CD4+ lymphocytes, which were presented as a significant sign of mycosis fungoides. Therefore, the aim of this study was to determine whether the CD8+-CD3+ ratio could be a marker for the diagnosis of mycosis fungoides, which excludes histiocytic component. Quantitative CD8+:CD3+ ratios were determined separately in the epidermal and dermal component of the skin biopsies of 5 patients with mycosis fungoides in the early stages of the disease. As the result we can estimate that CD8+:CD3+ ratio can be used in the differential diagnosis of mycosis fungoides and inflammatory dermatoses.